PENGARUH PENAMBAHAN BUBUR RUMPUT LAUT Ulva lactuca TERHADAP TINGKAT PENERIMAAN DAN GIZI KRIPIK - Nusaibah, Nusaibah - (MARLIN, 2025)
The aim of this research is to determine the best formulation and the effect of adding Ulva lactuca seaweed pulp on the acceptability and nutritional value of chips. In this study, 4 treatments were carried out with different concentrations of algal slurry, with F0 as control (without addition of U. lactuca slurry), F1 with addition of 20% slurry, F2 up to 40%, and F3 up to 50%. The parameters tested were hedonic tests, water content, protein content, fat content, ash content, crude fiber, carbohydrates and dietary fiber. The Kruskal-Wallis test is used in hedonic test data analysis. The test results showed that the best formulation of F3 was achieved with the highest fiber content, namely 31.74%, protein 6.98%, ash 1.30%, fat 26.45%, carbohydrates 63.32%, and the panelists liked in all parameters. The conclusion of this research is that the addition of seaweed pulp leads to an increase in fiber value and not a decrease in consumer preferences for all parameters.